THE EXPERIENCE OF FIGHTING THE SHADOW ECONOMY IN ENSURING THE ECONOMIC SECURITY OF THE RUSSIAN FEDERATION (World Bulletin of Social Sciences, 2021)
The scientific article is devoted to the experience of countering the shadow economy in ensuring the economic security of the Russian Federation. The article presents a detailed analysis of the definitions of the shadow economy in the Russian Federation by experts, regulatory legal acts aimed at countering the shadow economy in the country, as well as practical measures taken to combat the shadow economy in the country and their impact. The results obtained. The article also presents an analysis of the shadow economy in the Russian Federation by industry and region
Keywords: Shadow economy; market; currency; person